2013
DOI: 10.5121/ijwmn.2013.5507
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Macrocellular Network Densification on the Capacity, Energy and Cost Efficiency in Dense Urban Environment

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…The model extends the original horizontal pattern model of 3GPP, proposed in specification TS36.184, to include a vertical antenna pattern model with an option to set the electrical downtilt. The electrical tilt is computed for each of the macrocell intersite distance based on the methodology used in [12]. The Microcells and FAPs are assumed to employ an omni-directional antenna.…”
Section: E Antenna Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The model extends the original horizontal pattern model of 3GPP, proposed in specification TS36.184, to include a vertical antenna pattern model with an option to set the electrical downtilt. The electrical tilt is computed for each of the macrocell intersite distance based on the methodology used in [12]. The Microcells and FAPs are assumed to employ an omni-directional antenna.…”
Section: E Antenna Modelmentioning
confidence: 99%
“…The total power consumption of different network densification alternatives in LTE context was studied in [11], which concludes that under low discontinuous transmission (DTX), the macrocell densification is the most power efficient solution. In [12], a techno-economic study of macrocellular densification in a dense urban Manhattan type environment was reported, which highlights the performance limitations of macrocell networks in indoor environment. The techno economics of introducing femtocells into LTE macrocellular networks, with open access and closed access femto mode, have been studied in [13].…”
Section: Introductionmentioning
confidence: 99%
“…For the same multicast content dissemination, this pair of cellular channels will be interleaved on the relaying path from the base station to the final target DCH, which is not used by other multicast content distribution services, and thus, the cochannel interference will not occur. erefore, in this paper, we will ignore the cochannel interference in formulas (5) and (6) to simplify the calculation process of cellular multicast power and intercluster D2D multicast power.…”
Section: E Solving Methods For D2d Multicast Transmission Powermentioning
confidence: 99%
“…For t � 1 to T do (5) If k � argmax i∈ 1,...,K { } (g it ) then m tk � 1 End if (6) End for (7) For k � 1 to K do (8) x…”
Section: E Solving Methods For D2d Multicast Transmission Powermentioning
confidence: 99%
See 1 more Smart Citation